PENGARUH TEMPERATUR LAMA PENYIMPANAN TELUR PUYUH TETAS TERHADAP DAYA TETAS, FERTILITAS, BOBOT SUSUT TELUR DAN BOBOT TETAS TELUR PUYUH - Fitrah, Reza; Sudrajat, Deden; Anggraeni, Anggraeni (Universitas Djuanda Bogor, 2018)
Hatching is part of the nursery activity that is to maintain and increase the population of quail livestock. Research on the influence of old temperature of hatching quail egg to hatchability, fertility, egg shrink weight and weight of quail egg hatch has been done for one month, this research aim to know influence of temperature and duration of egg storage to fertility, hatchability, hatching weight, and Egg shrinkage weight in the quail and can know the temperature and long storage is good for hatched. This study used quail eggs (Coturnix coturnix japonica), as many as 180 items divided into two groups. Each is a group with a temperature of 27-30 oC and 17-20 oC group with egg storage duration (1 day, 3 days, and 6 days). The hatching machine used is semi-automatic hatching machine, before the egg is inserted into a hatching machine performed selection that includes egg shape and egg weight, for storage of 27-30 oC in room chamber and for 17-20 oC temperature in air-conditioned room with a temperature of 16 oC before the save egg in weigh and before inserted into the engine hatching the egg back in weigh. From 2 factors with three levels are obtained 6 treatment combinations each treatment - each treatment is repeated 5 times, each repetition consists of 6 grains. The experimental design used was Completely Randomized Design (RAL) 3 x 2 for fertility variable, hatchability, hatching weight and egg shrinkage. The results showed that the temperature gives a real effect on the hatchability, egg shrinkage, while for egg weight only gives a real effect on hatchability and shrinkage of eggs.Keyword: fertility variable, hatchability, hatching weight and egg shrinkage